Managing Carpal Tunnel Syndrome: Insights into Symptoms and Relief - Zaina Jose Elizabeth; Regina P.F.; Rose Jose (International Journal of Orthopedic Nursing and Practices, 2023)
Carpal tunnel syndrome (CTS) is a prevalent and concerning issue affecting the wrist and hand, arising from the compression of the median nerve within the carpal tunnel. This compression results in a spectrum of distressing symptoms, including numbness, tingling, weakness, and discomfort, particularly in the thumb, index, and middle fingers. Despite its frequent association with repetitive hand movements and prolonged use of computers or handheld devices, CTS can stem from various factors, encompassing genetic predisposition, underlying health conditions, and occupational risks. The abstract aims to delve into the management of CTS, offering insights into its symptoms and potential relief strategies. Prompt recognition and comprehension of symptoms are crucial for effectively managing this syndrome. Diagnostic measures, including clinical assessments and nerve conduction studies, aid in confirming the diagnosis and initiating appropriate interventions. Therapeutic approaches for managing CTS span a spectrum from conservative to surgical measures, depending on the severity of symptoms and the patient’s condition. Non-invasive methods such as wrist splinting, ergonomic adjustments, and lifestyle modifications often provide initial relief. Additionally, physical therapy and targeted exercises aim to alleviate discomfort and enhance wrist flexibility and strength. In cases refractory to conservative treatments, surgical interventions like carpal tunnel release may be considered to alleviate pressure on the median nerve, thereby mitigating symptoms and restoring hand function. This abstract strives to provide a comprehensive understanding of CTS management, emphasizing the importance of early recognition, lifestyle modifications, and a multi-disciplinary approach involving healthcare professionals. Educating individuals about preventive measures and ergonomic practices is paramount in minimizing the impact of CTS on daily activities and improving the overall quality of life.
Keywords: Carpal tunnel syndrome; Quality of life; healthcare professionals; lifestyle modifications